Analisis Kebutuhan Tempat Pembuangan Sampah Dan Alat Pengangkut Sampah Di Kelurahan Kertapati Palembang - Lega Reskita Lubis; Dimitri Yulianti (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Garbage accumulation certainly has a negative impact on the surrounding environment so that an adequate waste management system is needed. Poor waste management will cause disease, flooding and reduce environmental beauty. In addition to polluting the environment, garbage can also pollute the soil if it is burned and make the soil unhealthy. The smoke from burning garbage will also cause respiratory problems for the surrounding community. Before transporting the waste to the Final Disposal Site (TPA), the garbage is first collected by means of collection, such as garbage carts that pick up trash from houses to Temporary Disposal Sites (TPS) . At this time, the need for TPS and waste transportation equipment in Kertapati Village, is still experiencing many problems. The small number of TPS makes people litter. Garbage that has been wrapped in plastic is thrown away along the median of the Kertapati Village Palembang road. The garbage that is in the median of the road will be taken by the Palembang City Sanitation Service officer using a dump truck to the final disposal site (TPA). Garbage collection is carried out twice, namely in the morning and evening. The accumulation of garbage occurs due to a lack of landfills and inadequate means of collecting garbage. The results show that the number of additional TPS needed in Kertapati Village Palembang in 2019 is 3 units with a projected waste generation of 36,246 m3 / day. In 2024, the demand for TPS in Kerapati Village will increase to 4 TPS units with a projected waste generation of 44.875 m3 / day. The waste collection tool needed in the Keratapati Village, in the planning is 3 units. Keywords: Solid waste; Garbage Transport System